Persepsi Siswa dan Guru Terhadap Pelaksanaan Pembelajaran Berbasis E-Learning Di SMK Negeri 4 Jakarta - Gerry Krista Permana; Daryati Daryati (LPPM Universitas Negeri Jakarta, 2013)
The Objectives of this study to know the perceptions of students and teachers the learning implementation based on E – Learning in the SMK Negeri 4 Jakarta which has been applied for three years. Place of study was conducted at SMK Negeri 4 Jakarta in the month of August – September 2013. This study used a survey method with Likert scale 1-5. The population in this study were 60 students and 60 teachers of SMKN 4 Jakarta and the total sample of 30 students and 30 teachers are determined by the sampling technique using simple random sampling for a sample of teachers and for students using purposive sample technique. The instrument used was a questionnaire to capture the perception of students and teachers on the learning implementation based on E – Learning in SMK Negeri 4 Jakarta which has been applied for three years. Reliability of the results obtained from the calculation value of r 0.96 for the questionnaire distributed to the teachers and r 0.98 for questionnaire distributed to the students.The results of students and teachers perceptions study learning based on implementation of E – Learning in SMK Negeri 4 Jakarta, based on teachers respondent answers to perceptions of infrastructure aspects indicator have a mean value is 3.84. On the perception of the education management aspects indicators have a mean value is 3.59. In the perception of human resources aspects has a mean value is 3.49. Based on students respondent answers perceptions of the infrastructure aspects indicator has a mean value is 3.82. In the perception of the management aspects of education indicators have a mean value is 3.45. In the perception of human resources aspects has a mean value is 3.77.Based on the results of this study can be concluded that learning based on implementation of E – Learning in SMK Negeri 4 Jakarta is not well, because the Internet conection are sometimes being slow and disconnected, there are some teachers and students who do not understand about information technology and communication, also do not understand the procedure of learning implementation based on E - learning and there are still some students who do not have a laptop / net book thus hindering the learning process